2016
DOI: 10.1111/jcmm.12770
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: miR‐655 suppresses epithelial‐to‐mesenchymal transition by targeting Prrx1 in triple‐negative breast cancer

Abstract: Triple‐negative breast cancer (TNBC) is a highly aggressive breast cancer subtype that lacks effective targeted therapies. The epithelial‐to‐mesenchymal transition (EMT) is a key contributor in the metastatic process. In this study, we found that miR‐655 was down‐regulated in TNBC, and its expression levels were associated with molecular‐based classification and lymph node metastasis in breast cancer. These findings led us to hypothesize that miR‐655 overexpression may inhibit EMT and its associated traits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…Harazono et al (2013) [47] reported that the overexpression of miR-655, which is an EMT-suppressive miRNA that targets TGFBR2 and ZEB1, not only induced the up-regulation of E-cadherin and the downregulation of typical EMT inducers but also inhibited the invasion and migration of mesenchymal-like cancer cells. Furthermore, the upregulation of miR-655 inhibits cell invasion in esophageal squamous cell carcinoma [48], triple-negative breast cancer [49], and hepatocellular carcinoma [50]. MiRNA-455 (miR-455) is recognized as a broadly conserved noncoding RNA that has been implicated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Harazono et al (2013) [47] reported that the overexpression of miR-655, which is an EMT-suppressive miRNA that targets TGFBR2 and ZEB1, not only induced the up-regulation of E-cadherin and the downregulation of typical EMT inducers but also inhibited the invasion and migration of mesenchymal-like cancer cells. Furthermore, the upregulation of miR-655 inhibits cell invasion in esophageal squamous cell carcinoma [48], triple-negative breast cancer [49], and hepatocellular carcinoma [50]. MiRNA-455 (miR-455) is recognized as a broadly conserved noncoding RNA that has been implicated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the upregulation of miR‐183‐5p induced apoptosis and inhibited EMT, proliferation, invasion, and migration by the downregulation of ezrin in human endometrial cancer cells . Collectively, EMT is inhibited by many miRNAs, including miR‐145, miR‐497, miR‐145‐5p, miR‐138, miR‐200a, miR‐200b, miR‐655, miR‐30‐5p, and miR‐32 . In addition, EMT is also promoted by many miRNAs, including miR‐221, miR‐222, miR‐214‐3p, and miR‐181a …”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…194 Collectively, EMT is inhibited by many miRNAs, including miR-145, miR-497, miR-145-5p, miR-138, miR-200a, miR-200b, miR-655, miR-30-5p, and miR-32. [195][196][197][198][199][200][201] In addition, EMT is also promoted by many miRNAs, including miR-221, miR-222, miR-214-3p, and miR-181a. [202][203][204] The flavonoids rhamnetin from cloves, berries and cirsiliol from Cirsium lineare (Thunb.)…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…carcinoma (19,20), triple-negative breast cancer (21) and esophageal squamous cell carcinoma (22). However, the expression, role and molecular mechanisms of miR-655 in OSCC have not yet been elucidated.…”
Section: Microrna-655 Suppresses Cell Proliferation and Invasion In Omentioning
confidence: 99%